STUDI ANATOMI TANAMAN KOMAK KEDIT (Phaseolus lunatus L.) LOKAL DI PULAU LOMBOK - Sri Warni; Muhammad Junaedi (LPPM Universitas Negeri Jakarta, 2023)
Plant anatomy is one of the important basic data to reveal the potential of a plant. Anatomical data provide an overview of the internal structure of the plant body. This structure is influenced by the environment, the same thing is also likely to occur in Komak kedit plants which are widely planted on Lombok Island. Komak kedit (Phaseolus lunatus L.) is a species of legume (Fabaceae) originating from Central America. The purpose of this study was to analyze the differences or variations in the anatomical structure of the Komak kedit (P. lunatus) on Lombok Island. Data analysis in this research was descriptive qualitative and triangulation. The results showed that the anatomical structure of the roots, stems, leaves, flowers, fruits, and seeds of the Komak kedit plant on Lombok Island had similar structure, such as epidermis, cortex, and stele. However, in this study, there were more differences in the number of stomata on leaves in West Lombok compared to East Lombok, Central Lombok, North Lombok, and Mataram. This was caused by differences in the environment where the plants were planted, such as water content.